On New Ways of Hlbina´s Poetry - Peter Tolarovič (Slovenska Literatura, 2021)
The paper deals with the poetry of Pavol Gašparovič Hlbina written in the second half of the 1930s, when the author was one of the most productive Slovak poets, reviewers, translators, and literary aestheticians. It traces the causes of changes in his poetics used especially in the collection of poems Dúha (The Rainbow, 1937) as well as his relations to his close collaborator Rudolf Dilong (1905 – 1986), mainly in the context of their editorial activities in the magazines associated with Catholic Modernism (Postup and Prameň). It outlines the author´s poetry in the context of Slovak modification of poetism and maps his views on surrealism. When the collection Dúha (The Rainbow, 1937) was published, Hlbina was closely following the rising surrealist tendencies in the Slovak literary environment and writing numerous reflections on them. This collection of poems also represents the modern variant of his poetry. The other variant is religious poetry; this type of poetics was used when cooperating on an extensive project of St Adalbert Association, which was the Unified Catholic Hymnbook published in 1937.